1999
DOI: 10.1002/(sici)1098-2361(1999)18:4<335::aid-zoo8>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral differences as predictors of breeding status in captive cheetahs

Abstract: Individual behavioral variation of 44 adult captive‐born cheetahs, Acinonyx jubatus, was assessed using observer and keeper ratings on a variety of behavioral attributes. Inter‐rater consensus was high for most questionnaire items, several of which were significantly correlated with direct behavioral measures recorded in a mirror‐image experiment. Principal component analysis was applied to identify patterns of individual variation as measured by observer and keeper ratings. Three major components, labeled as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
146
2
3

Year Published

2002
2002
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 155 publications
(160 citation statements)
references
References 72 publications
9
146
2
3
Order By: Relevance
“…Shyness tended to be higher in giant pandas living in enclosures with only one den site, suggesting that changes in enclosure features might have a positive impact on personality and improve reproductive success. Wielebnowski (1999) found that nonbreeding cheetahs were rated by their keepers as being significantly more tense or fearful than breeding cheetahs.…”
Section: Powell and Svokementioning
confidence: 92%
See 2 more Smart Citations
“…Shyness tended to be higher in giant pandas living in enclosures with only one den site, suggesting that changes in enclosure features might have a positive impact on personality and improve reproductive success. Wielebnowski (1999) found that nonbreeding cheetahs were rated by their keepers as being significantly more tense or fearful than breeding cheetahs.…”
Section: Powell and Svokementioning
confidence: 92%
“…More often, the assays rely on measuring animal responses to some form of novelty (exposure to novel environments, stimuli, conspecifics, humans) or to stimuli that are known to be stressful. In recent years, there has been an effort to try to validate keeper or caretaker assessments of personality (Carlstead, Mellen, et al, 1999;Momozawa et al, 2003;Wielebnowski, 1999). In most studies, human evaluations of animal personality are reliably correlated with at least some behavioral characteristics of animals (but see Seaman, Davidson, & Waran, 2002).…”
Section: Powell and Svokementioning
confidence: 99%
See 1 more Smart Citation
“…There is now substantial evidence suggesting a large variation amongst individuals' behaviours within species and breeds (Manteca and Deag, 1993;Wielebnowski, 1999;Buffington, 2002;Serpell and Hsu, 2005;King et al, 2012).…”
Section: 0mentioning
confidence: 99%
“…These behavioural differences arise from variation in temperament traits and may significantly affect the way individuals interact with the environment, thereby influencing Darwinian fitness (e.g. Armitage, 1986;Carlstead, Mellen & Kleiman, 1999b;Wielebnowski, 1999;R´eale et al, 2000;Dingemanse et al, 2004). Building on previous ideas (e.g.…”
Section: Introductionmentioning
confidence: 99%